Maxillary osteosarcoma: a case report and review of maxillary sinus space-occupying lesions - Shokri, Abbas; Ramezani, Kousar (Brazilian Dental Science, 2020)
Osteosarcoma is a relatively rare lesion in the maxillary bone. The proximity of the lesion to the maxillary sinus provides a null space with the minimum resistance to progress prior to manifest clinically, which makes the early diagnosis more critical. We report a case of maxillary osteosarcoma in a 21-year old male patient who was presented with the chief complaint of the pain and swelling on the left side of palate since 2 months earlier. A cone-beam computed tomography of the maxilla revealed a diffuse hyper-intense entity at the left side of the maxilla. Totally-occupied maxillary sinus space, asymmetric periodontal ligament widening of the involved teeth and spiculated and sunray periosteal reaction were recognized. The diagnosis of osteosarcoma was established and confirmed by histopathology. This article reviews the sinus-occupying lesion in the following and describes the lesions originate within the maxillary sinus or arise from the adjacent odontogenic components.KeywordsCase report; Maxillary sinus; Osteosarcoma.